Fiscal Capability of the SOCCSKSARGEN Region in Implementing Local Development Programs - Garcia, Beverly (Journal of Interdisciplinary Perspectives, 2025)
This study, titled "Fiscal Capability of the SOCCSKSARGEN Region in Implementing Local Development Programs and Projects," examined the region’s capacity to generate, allocate, and manage financial resources for effective local development. Recognizing fiscal capability as a vital driver of regional growth, the research assessed how well the region supports programs aimed at economic progress, infrastructure development, and social services. Employing a quantitative descriptive-correlational design, the study utilized mean scores to evaluate levels of fiscal capability and Spearman Rank Correlation to examine relationships between fiscal performance and development outcomes. Results indicate a high level of fiscal capability in program implementation. However, challenges such as limited local revenue sources, reliance on national transfers, and inefficiencies in budget execution were also identified. The study recommends strengthening local revenue generation, improving budget allocation processes, and implementing strategic financial planning at the regional level. Capacity-building programs for local government units (LGUs), along with enhanced transparency and participatory budgeting mechanisms, are suggested to ensure long-term fiscal sustainability. The research contributes to a broader understanding of regional fiscal management within the framework of local development, offering insights for policymakers and planners in similar socioeconomic contexts. It underscores the importance of efficient and accountable fiscal systems in achieving sustainable development and improving the quality of life in local communities.